2012
DOI: 10.1002/env.2167
|View full text |Cite
|
Sign up to set email alerts
|

A model for spatio‐temporal clustering using multinomial probit regression: application to avalanche counts

Abstract: Although modeling complex environmental spatio‐temporal processes, separability between time and space effects is often assumed as a first approach, even though it may be unrealistic. Hence, the development of adapted non‐separable spatio‐temporal models is a challenging issue. In this work, we are interested in modeling avalanche counts over the whole French Alps, a large area that exhibits zones characterized by distinct climatic behaviors. We have at our disposal a data set of 405, 63‐year series of avalanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 30 publications
1
27
0
2
Order By: Relevance
“…Le « recul des avalanches » ensuite observé, accompagné d'une diminution de la proportion des avalanches avec aérosol s'inscrit quant à lui dans une période de réchauffement marqué. Enfin, depuis quelques années (2000) Ce schéma global masque en réalité des évolutions différenciées contrôlées par l'altitude [Lavigne et al, 2012 ;2015]. A basse altitude, la réduction d'activité depuis 1980 environ a été drastique, en lien avec la forte réduction de l'enneigement induite par le réchauffement climatique.…”
Section: Reponse De L'activité Avalancheuse Aux éVolutions Du CLIunclassified
“…Le « recul des avalanches » ensuite observé, accompagné d'une diminution de la proportion des avalanches avec aérosol s'inscrit quant à lui dans une période de réchauffement marqué. Enfin, depuis quelques années (2000) Ce schéma global masque en réalité des évolutions différenciées contrôlées par l'altitude [Lavigne et al, 2012 ;2015]. A basse altitude, la réduction d'activité depuis 1980 environ a été drastique, en lien avec la forte réduction de l'enneigement induite par le réchauffement climatique.…”
Section: Reponse De L'activité Avalancheuse Aux éVolutions Du CLIunclassified
“…In Lavigne et al . (), based on the hypothesis that avalanche frequency temporal trends should be different in the two subregions, a model‐based clustering approach was designed. In Eckert et al .…”
Section: Introductionmentioning
confidence: 97%
“…In the French Alps, data coming from a systematic survey of avalanche events which began at the beginning of the 20th century is available. However, even though adapted probabilistic models are now well developed (Eckert et al ., , ; Eckert, Parent, Kies and Bays, ; Lavigne et al ., ), complementary expertise is needed to account for the specific complexity of the entire region.…”
Section: Introductionmentioning
confidence: 99%
“…[ Beniston , ; Adam et al , ; Bebi et al , ; Keiler et al , ; Stoffel and Huggel , ]. Climate change is therefore likely to influence the occurrence of damage due to avalanches; however, the exact trend remains undecided and will be highly dependent on the region concerned [ Lavigne et al , ; Castebrunet et al , ; McClung , ]. Some studies have concluded that there is no clear correlation between the frequency of extreme events and climatic conditions [ Schneebeli et al , ; Eckert et al , ], whereas others have provided evidence that the runout distance of extreme avalanches has decreased since the mid‐1970s [ Eckert et al , ].…”
Section: Introductionmentioning
confidence: 99%